Toll-Like Receptors Regulate the Development and Progression of Renal Diseases - Minghui Liu; Ke Zen (Karger Publishers, 2020)
Background: Stimulated by both microbial and endogenous ligands, toll-like receptors (TLRs) play an important role in the development and progression of renal diseases. Summary: As a highly conserved large family, TLRs have 11 members in humans (TLR1∼TLR11) and 13 members in mouse (TLR1∼TLR13). It has been widely reported that TLR2 and TLR4 signaling, activated by both exogenous and endogenous ligands, promote disease progression in both renal ischemia-reperfusion injury and diabetic nephropathy. TLR4 also vitally functions in CKD and infection-associated renal diseases such as pyelonephritis induced by urinary tract infection. Stimulation of intracellular TLR7/8 and TLR9 by host-derived nucleic acids also plays a key role in systemic lupus erythematosus. Given that certain microRNAs with GU-rich sequence have recently been found to be able to serve as TLR7/8 ligands, these microRNAs may initiate pro-inflammatory signal via activating TLR signal. Moreover, as microRNAs can be transferred across different organs via cell-secreted exosomes or protein-RNA complex, the TLR signaling activated by the miRNAs released by other injured organs may also result in renal dysfunction. Key Messages: In this review, we sum up the recent progress in the role of TLRs in various forms of glomerulonephritis and discuss the possible prevention or therapeutic strategies for clinic treatment to renal diseases.